Food, Identity and Femininity: Sicily as a Woman - García Fernández, José (2026)
Published by Giuseppina Torregrossa in 2007, L’assaggiatrice is the debut novel of a Palermitan writer who has consistently explored the female figure in the narrative plots of her works. Methodologically based on the philological examination of this first volume, this article analyzes the way in which Anciluzza, the central character of the story, behaves: abandoned by her husband and highly self-critical, the protagonist gradually begins to conceive of the world in a very different way. Sexuality, self-management, access to the labour market, and awareness of her personal worth shape the identity of a new woman whose femininity is intrinsically linked to Sicilian cuisine.